2012
DOI: 10.1088/1748-6041/7/5/054107
|View full text |Cite
|
Sign up to set email alerts
|

Adipogenic differentiation of scaffold-bound human adipose tissue-derived stem cells (hASC) for soft tissue engineering

Abstract: Adipose tissue engineering, instead of tissue substitution, often uses autologous adipose tissue-derived stem cells (hASC). These cells are known to improve graft integration and to support neovascularization of scaffolds when seeded onto biomaterials. In this study we thought to engineer adipose tissue using scaffold-bound hASC, since they can be differentiated into the adipocyte cell lineage and used for soft tissue regeneration. We show here by microscopy and gene expression of the peroxysome proliferator-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
(55 reference statements)
1
8
0
Order By: Relevance
“…Furthermore, the presence of GFP+ve cells can be confirmed in the new tissue, indicating that the ASC is, at a minimum, retained within the forming tissue and has a positive effect on adipose generation. Similar findings have also been reported using ASCs in combination with a variety of scaffolds including silk fibroin, collagen type 1, collagen/gelatin, alginate, polypropylene, and scaffolds modified for the controlled release of growth factors such as bFGF [218][219][220][221][222]. Human ASCs have also been used to form fat using a "self-assembly" approach in which the ASC is used to produce not only adipocytes but also its own supportive stroma [223].…”
Section: In Vivo Fat Regenerationsupporting
confidence: 67%
“…Furthermore, the presence of GFP+ve cells can be confirmed in the new tissue, indicating that the ASC is, at a minimum, retained within the forming tissue and has a positive effect on adipose generation. Similar findings have also been reported using ASCs in combination with a variety of scaffolds including silk fibroin, collagen type 1, collagen/gelatin, alginate, polypropylene, and scaffolds modified for the controlled release of growth factors such as bFGF [218][219][220][221][222]. Human ASCs have also been used to form fat using a "self-assembly" approach in which the ASC is used to produce not only adipocytes but also its own supportive stroma [223].…”
Section: In Vivo Fat Regenerationsupporting
confidence: 67%
“…32 To control negative effects of ion dissolution products of 45S5 Bioglass Ò , we began by preconditioning of the scaffolds and hernia meshes. When the cell suspension of hASC finally was mixed with collagen and seeded onto the preconditioned scaffolds, cell seeding resulted in a dense layer of hASCs (Fig.…”
Section: Hasc Adhesion and Proliferation On Fibrous And 45s5 Bioglassmentioning
confidence: 99%
“…6 To determine whether potential effects in our CAM angiogenesis assay were due to these ion dissolution products or other material-specific characteristics, we used conventional biologically inert polypropylene hernia meshes as a control material. For a plain biofunctionalization of the scaffold materials, we referred to a previously published technique, 32 where cell adhesion on the polypropylene meshes could be clearly enhanced by coating them before seeding with collagen containing extracellular matrix-like coating. Leu and Leach, 13 as well as Yao et al 37 already showed that collagen does not produce false-positive angiogenic side effects: Sponges made of collagen type-1 improved neither endothelial cell proliferation, HUVEC tube formation or an upregulation of VEGF production in coculture experiments in vitro 13 nor an ingrowth of blood vessels in the CAM angiogenesis assay in vivo.…”
mentioning
confidence: 99%
“…28 An important aspect of adaptive reshaping is the vascularization of adipose tissue responsible for the resorption of all types of grafts (autologous, allogenic, or alloplastic). The use of autologous and allogenic grafts, unlike scaffolds composed of biomaterials, is more susceptible to immune rejection, allergic reactions, implant migration, inability to integrate into adjacent tissues, and repetition of the surgical procedure to maintain the volume of the adipose tissue and of any another type of soft tissue.…”
Section: Scaffolds: Physical and Substrate Porous Supports For Seedinmentioning
confidence: 99%
“…32,33 The use of scaffolds in tissue engineering is a promising option for the temporary replacement of adipose tissue in postoperative conditions, congenital problems, or post-traumatic lesions, favoring regeneration of the native tissue. 34,35 The scaffold, as a carrier, could serve to veiculate microcapsules of autologous stem cells such as those obtained by Handel et al 28 Choi et al 36 implanted a collagen scaffold containing autologous adipose cells. The scaffold promoted proliferation of the stem cells, demonstrating the potential of this procedure for the production of adipose tissue.…”
Section: Scaffolds: Physical and Substrate Porous Supports For Seedinmentioning
confidence: 99%